UTILIZATION OF RADIOSONDE DATA TO PREDICT LLWS EVENTS IN THE JUANDA AIRPORT AREA - Didik Kurniawan; Khisom Adi Purwanto; Yosafat Dony Hartanto (Politeknik Penerbangan Surabaya, 2025)
Low-Level Wind Shear (LLWS) is one of the dangerous atmospheric phenomena that can interfere with flight safety, especially during takeoff and landing phases. This study aims to evaluate the potential of radiosonde data processed using RAOB software as a tool to predict the occurrence of LLWS in the Juanda International Airport area. The study used a correlational descriptive method with radiosonde data and LLWS incidence data from the LLWAS system for the 2023–2024 period. The results of the analysis showed that atmospheric parameters such as TPW, LCL, LI, and KI had a significant relationship with LLWS occurrence. The model produces a high precision value (0.99), but a low recall (0.35), which suggests that although the model is able to accurately identify LLWS, there are still many undetected LLWS events. Thus, radiosonde data has potential as an aid to LLWS prediction, but it needs to be further developed to improve its sensitivity and effectiveness in early warning systems.